Warunki dobrego postu według wybranych pisarzy greckich IV-VI w. - Widok, Norbert (Vox Patrum, 2020)
The practice of fasting among the followers of Jesus Christ was a significant ascetic activity starting from the first generations of Christianity, because this recommendation appeared in the teaching of the Saviour. That is why spiritual shepherds of those times variously encouraged members of their communities to fast from time to time, regardless of their diverse attitudes to it. The presence of the issue of fasting in the ecclesiastical life of those communities is evidenced by homilies, speeches and treatises, in which the faithful are told how to perceive the principles of fasting and its healing properties. The authors who dealt with those issues were, for example, Asterius of Amasea (4th–5th c.), Marcus Eremita (5th c.), Pseudo-Chrysostom (5th–6th c.) and Pseudo-Eusebius of Alexandria (5th–6th c.). In their writings, they left a lot of information on Christian spirituality, as well as numerous pieces of practical advice regarding the inclusion of fasting in everyday life. The presented text contains a description of the initial stage, i.e., the conditions and requirements for undertaking fasting, which ultimately are expected to bring measurable benefits to the soul and body. For these reasons, the authors of these speeches wanted to raise the awareness of their recipients for them to form a positive attitude towards fasting.